Management information systems errors. Scientometric analysis (Revista de Investigaciones Universidad del Quindío, 2022)
The purpose of this articles is to identify errors related to management information systems through a Scientometric analysis to divulge the dynamics of the research topic to the academic community. The study was carried out, between 1971 and January 30, 2021, using the Scopus database and VOSviewer software. As a result of the search string "management information system" and “error*” or "mistakes" were obtained 826 published scientific articles. The highest percentage of documents published are conference paper (53.3%), and Article (39.7%). The most productive countries are the United States and Austria (60% articles) and citations are focused on United States (65%). The chronological analysis revealed that the scientific production in the area showed a particular increase from 2006 to 2009. The Lecture Notes in Computer Science. Lecture notes in Artificial Intelligence and Lecture Notes in Bioinformatics was the most productive journal. The 32.7% of the literature was published in the Computer Science field. 6 clusters were identified, and 19 keywords related with errors or mistakes were recognized. The Scientometric analysis accomplished allowed a descriptive analysis and identification of the countries, journals, keywords, sponsors, most cited articles, clustering the results facilitating the visual representation of the study.
Keywords: Scientometric; management information systems; mistake; error; fault